PENGELOLAAN CARA PANDANG SISWA TERHADAP BIMBINGAN KONSELING (BK) MELALUI LAYANAN INFORMASI BAGI SISWA MA - Herni Yusnita (UNIVERSITAS BENGKULU, 2017)
The research objective of this class action is to facilitate the management of students' perspective towards Counseling (BK) for students of classes X Madrasayh Aliyah Public 2 Bengkulu City. This classroom action research conducted in MA Public 2 Bengkulu City. The method used in the study of this class action is to provide some action on information services. Subjects were students of class X Madrasah Aliyah Public 2 Bengkulu city, amounting to 36 students. The results showed that information services can work to change the way students of the Guidance and Counseling from the poor and afraid to come alone (consultation) into the perspective of the Counseling well and be a friend to the students, it can be concluded both theoretically and empirically that through information services may seek conversion of perspective students to the Counseling for students of classes X Madrasah Aliyah Public 2 Bengkulu City.en